Origins and Outcomes of Electoral Institutions in African Hybrid Regimes: A Comparative Perspective - Alexander Stroh; Sebastian Elischer; Gero Erdmann (German Institute of Global and Area Studies (GIGA), 2012)
In the early 1990s most African countries carried out extensive reforms of their electoral regimes. Adopting a historical institutionalist approach, this paper critically examines the role of institutional path dependence in accounting for the setup of six African electoral regimes. For this purpose, we distinguish between different types of path dependence. The paper further analyzes the extent to which the development of electoral institutions contributed to the regime-type outcome (democratic/hybrid/autocratic). The main emphasis herein is on so-called hybrid regimes; in other words, regimes existing in the grey zone between democracy and autocracy. The paper finds that, while institutional path dependence has a limited but important impact on the setup of the electoral regimes, it is ultimately the process of decision-making during critical junctures that accounts for the regime type outcome. Hybrid regimes lack long-term institutional ownership.
Keywords: 300; hybrid regimes; democratization; historical institutionalism; electoral institutions; Africa; Wahlsystem; Reform; Politisches System; Demokratisierung; Institutionalismus; Pfadabhängigkeit; Afrika